2016
DOI: 10.3847/0004-637x/825/1/64
|View full text |Cite
|
Sign up to set email alerts
|

On the Social Traits of Luminous Blue Variables

Abstract: In a recent paper, Smith & Tombleson (2015) state that the Luminous Blue Variables (LBVs ) in the Milky Way and the Magellanic Clouds are isolated; that they are not spatially associated with young O-type stars. They propose a novel explanation that would overturn the standard view of LBVs. In this paper we test their hypothesis for the LBVs in M31 and M33 as well as the LMC and SMC. We show that in M31 and M33, the LBVs are associated with luminous young stars and supergiants appropriate to their luminosities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 72 publications
8
114
0
Order By: Relevance
“…These include all confirmed LBVs in the LMC and likely, wellstudied LBV candidates with shells. We exclude the five unrelated stars and the duplicate entry pointed out by Humphreys et al (2016), bringing the total number to ten LBVs -three classical LBVs and seven lower-luminosity LBVs. In M33, there are only four confirmed LBVs (Hubble-Sandage variables B, C and 2 and Var 83; Humphreys et al 2014), but we include them as well (the actual number of LBV stars in M33 was estimated to be in the hundreds by Massey et al 2007).…”
Section: Other Evolved Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include all confirmed LBVs in the LMC and likely, wellstudied LBV candidates with shells. We exclude the five unrelated stars and the duplicate entry pointed out by Humphreys et al (2016), bringing the total number to ten LBVs -three classical LBVs and seven lower-luminosity LBVs. In M33, there are only four confirmed LBVs (Hubble-Sandage variables B, C and 2 and Var 83; Humphreys et al 2014), but we include them as well (the actual number of LBV stars in M33 was estimated to be in the hundreds by Massey et al 2007).…”
Section: Other Evolved Starsmentioning
confidence: 99%
“…To reconcile this with the identified massive LBV progenitors of type IIn SNe, Smith & Tombleson (2015) examined the LBVs in the Large Magellanic Cloud (LMC) and found them to be relatively isolated from O-type stars, which was argued to at least partially explain the weak correlation with H α emission for the SNe. However, Humphreys et al (2016) pointed out that this LBV sample included both classical and lower-luminosity Original continuum-subtracted H α intensity maps used in this study: the LMC on the left (from the SHASSA survey; Gaustad et al 2001) and M33 on the right (Hoopes & Walterbos 2000), cropped in the case of the LMC but otherwise unaltered. North is up and east is left.…”
Section: Introductionmentioning
confidence: 99%
“…Humphreys et al (2016) showed that the confirmed LBVs in M31 and M33 were found primarily in stellar groups. We have added information about the stars' spatial identification with stellar groups such as known H II regions and Associations to Tables 2 and 3.…”
Section: The Spatial Distributionmentioning
confidence: 99%
“…LBVs are distinguished from the normal supergiants that occupy the same locus in the luminosity-temperature space by their proximity to the Eddington limit. They have high L/M ratios, and their Eddington factor Γ = L/L Edd is high, 0.5 or higher due to high mass loss events as hot supergiants for stars with initial masses ≥ 40 -50 M ⊙ or as red supergiants for the less luminous LBVs; see Figure 1 and the discussions in Humphreys et al (2016) and .…”
Section: The Hr Diagramsmentioning
confidence: 99%
See 1 more Smart Citation